Energy system contributions and determinants of performance in classical sprint cross-country skiing - Andersson, E.; Willis, S. J.; Holmberg, H. C.; Ørtenblad, N. (19th Annual Congress of the European College of Sport Science (ECSS), Amsterdam, 2. - 5. July 2014, 2014)
Introduction: Performance in sprint cross-country skiing (XCS) is related to oxygen uptake (VO2), oxygen deficit (OD), and gross efficiency (GE) (Losnegard et al., 2012). To the best of our knowledge, the relative importance of these factors in classical sprint XCS involving the double poling (DP) and the diagonal stride (DS) techniques have not been examined. Therefore, this study aims to address this. Methods: Eleven male cross-country skiers were tested on three different days and all tests were performed in the DP and the DS skiing techniques on a treadmill. Test-day one consisted of five sub-maximal stages, to assess GE, followed by an incremental VO2max test. Test-day two consisted of maximal velocity (Vmax) tests together with two time-trials as a familiarization. Test-day three consisted of four sprint timetrials (TT) over 1300 m including 3 DP sections (1° incline) and 2 DS sections (7° incline) separated by 45 minutes. Data from all four TT were averaged. Treadmill speed and VO2 were measured continuously during the TT in order to estimate OD. To assess the relative importance of different variables, a Pearson`s correlation analysis and a hierarchical multiple regression were performed. Results: The GE in DP at 22 km/h and in DS at 8.5 km/h were 15.6 ± 1.2% and 19.8 ± 0.9%, respectively. The VO2max was 65 ± 4 ml/kg/min in the VO2max test and 67 ± 3 ml/kg/min in the TT. DP Vmax was 33 ± 2 km/h and DS Vmax was 18 ± 1 km/h. The TT time was 232 ± 10 s (56% DP and 44% DS) and the DP and DS velocities were 27 ± 1 km/h and 14 ± 1 km/h, respectively. Accumulated VO2 and OD were 201 ± 10 and 58 ± 15 ml/kg, respectively, or 78 ± 5% and 22 ± 5% of the total energy demand. The Vmax in DP and DS was negatively correlated to TT time (r = -0.79 and -0.57, both P < 0.05). The multiple regressions demonstrated that the variance in TT time was related to GE by 38%, VO2 by34% and OD by 23% (r2 = 0.95, P < 0.05). Discussion: The relative energy contribution in the present study was similar to previous findings for uphill DS skiing and ski-skating (McGawley and Holmberg, 2014; Losnegard et al., 2012). Although Losnegard et al. (2012) concluded that OD explained 66-75% of the variance in TT time, we found OD to explain only 23% of this variance, with GE and VO2 together explaining 72%. Furthermore, the largest inter-individual differences were observed for the OD, range: 33-78 ml/kg. Finally, the correlations between Vmax and TT time highlight the importance of a high speed generation for sprint XCS performance.